Monitoring plant functional diversity from space - Jetz, Walter; Cavender-Bares, Jeannine; Pavlic, Ryan; Schimel, David; Davis, FranK W.; Asner, Gregory P.; Guralnick, Richard; Kattge, Jena; Latimer, Andrew M.; Moorcroft, Paul; Schaepman, Michael E.; Schildhauer, Mark P.; et al. (Nature Publishing Group, 2016)
The world’s ecosystems are losing biodiversity fast. A satellite mission designed to track changes in plant functional diversity around the globe could deepen our understanding of the pace and consequences of this change and how to manage it.